Pendampingan Administrasi untuk Menciptakan Budaya Tertib Administrasi Pada Kelompok Ternak “Ruminan Jaya Makmur” - Solikin, Nur; Linawati, Linawati (Universitas Nusantara PGRI Kediri, 2022)
In an organization, good administration is needed. Administration assists organizations in planning and development. Awareness of the importance of good administration, must exist and be understood by all members of the organization. Real portraits in the community, there are still organizations that have not or even not run their administration properly. There is no record of data or activities that have been and will be carried out, resulting in doubts about the existence of the organization. This community service activity was carried out at the “Ruminan Jaya Makmur” Livestock Group, Semen Village. The activity aims to increase the knowledge and understanding of all group members about administration, increase awareness to apply a culture of orderly administration, as well as compiling record books for the benefit of livestock group administration. Implementation of integrated activities for 1 month. Activities are packaged in the form of assistance, beginning with socialization of a culture of orderly administration and assistance in the preparation of books, records of livestock group activities. The implementation of the activity went smoothly and can be said to be successful. The achievement of the implementation of the activity was shown in the level of attendance of the participants and the high enthusiasm of all participants who attended and took part in the socialization activities. Assistance in the preparation of books, notes on group activities, manifested in the compilation of books and administrative records of the “Ruminan Jaya Makmur” Livestock Group, including the Guest Book, Member and Management List Book, Meeting Attendance List and Meeting Minutes, Member Dues Book, and Cash Book.